Antibacterial Activity and Phytochemical Analysis of Moringa oleifera Extract against Staphylococcus aureus Identified by Routine and Molecular Methods - Sawsan Qahtan Taha Al-Quhli; Omar Salim Ibrahim; Atheer A. Khashan (Medical Journal of Babylon, 2024)
Background:Many diseases caused by bacterial and viral infections may now be treated using herbal extracts instead of chemical drugs. Objectives:This study aimed to investigate the antibacterial effect of Moringa oleifera leaf extracts against the bacterium employed in the experiment, as a commensal. Staphylococcus aureus can be found on the skin and in the nasal flora. It can also cause invasive, localized illnesses. Many virulence factors are present in S. aureus. It is recognized by routine and molecular methods depending on Vick Staphylococcal gene. Material and Methods:Phytochemical analysis of high polarity solvent leaves was done by using ethanol. Phytochemical study revealed the presence of tannins, alkaloids, flavonoids, steroids, saponins, and other compounds in the extract. Using the well-diffusion method, the antibacterial effect of the extracts on microorganisms was investigated. Results:The ethanol extract proved potent against pathogenic microorganisms, with S. aureus showing the highest activity (10–100 mg/mL). In comparison to the concentrations of alcoholic extracts, the zones’ inhibition of bacterial growth in diameters increased. However, dosages of 80–100 mg/mL were highly effective and significant against S. aureus growth, whereas concentrations of 10–20 mg/mL had low post-detected efficiency and concentrations of 40–60 mg/mL had medium post-detected efficiency. Conclusion:These studies demonstrate the validity of the plant’s traditional medicinal properties.